Inovasi Buku Digital dalam Pendidikan Seni Tari Bagi Calon Guru SD - Tarmizi, Pebrian; Anggraini, Dwi; Firdaus, Ahdiat; Pertiwi, Ella Cahaya (UNIB Press, 2025)
This study aims to develop teaching materials for the Dance Arts Education course in elementary schools that are packaged digitally and adjusted to the characteristics of PGSD students and the characteristics of elementary school students. The research method used is the ADDIE model research and development method (Analysis, Design, Develop, Implementation Evaluation). In this study, the aspects of feasibility and practicality were measured. The research sample was students of the S1 PGSD Study Program Semester 3A as the control class and 3B as the experimental class taking the Dance Arts Education course in elementary schools. The results showed that the results of the material expert validation were 0.85 (very valid) with an agreement level of 66.67% (strong), the results of the graphic validation were 0.75 (moderate) with an agreement percentage of 66.67% (strong), and the results of the language validation were 0.90 (very valid) with an agreement percentage of 83.33% (very strong). The percentage of student responses to digital teaching materials for Dance Arts Education in Elementary Schools, namely the material aspect 91.67% (very practical), interestingness 86.25% (very practical) and language 70% (practical). Thus it can be concluded that the teaching materials developed are feasible and practical to use.